Occupational practitioner's role in the management of a crisis: lessons learned from the Paris November 2015 terrorist attack - Alexis Descatha; Alexis Descatha; Alexis Descatha; Alice Huynh Tuong; Service Médical du Raid; Pierre Coninx; michel Baer; Thomas Loeb; thomas Despréaux; thomas Despréaux (Frontiers Media S.A., 2016)
In massive catastrophic events, occupational health practitioners are more and more frequently involved in the management of such situations. We aim to describe the multiple aspects of the role that occupational health practitioners might play, by focusing on the recent example of the Paris terrorist attack of November 2015.During and after the Paris attack, occupational practitioners in collaboration with emergency and security professionals were involved in psychological care, assembling information, follow-up, return-to-work, and improving in-company safety plans.Based on this experience and other industrial disasters, we distinguish three phases: the critical phase, the post-critical phase, and the anticipation phase. In the critical phase, the occupational practitioner cares for patients before the emergency professionals take charge, initiates the psychological management, and may also play an organizational role for company health aspects. In the post-critical phase, he or she would be involved in monitoring those affected by the events, and participate in preventing, to the extent possible, post-traumatic stress disorder, helping victims in the return-to-work process, and improving procedures and organizing drills. In addition to their usual work of primary prevention, occupational practitioners should endeavor to improve preparedness in the anticipation phase, by taking part in contingency planning, training in first aid, and defining immediately applicable protocols.In conclusion, recent events have highlighted the essential role of occupational health services in anticipation of a crisis, management during the crisis, and follow-up.